On the Effect of Labour Productivity on Growth: Endogenous Fluctuations and Complex Dynamics - F. Grassetti; C. Mammana; E. Michetti (Discrete Dynamics in Nature and Society)
This paper introduces a sigmoidal production function that considers production possible even when the only input is labour. The long-run behaviour of an economy described by the neoclassical Solow-type growth model with differential savings is investigated considering the technology presented. It is found that labour productivity influences the existence of boom and bust periods as well as the level of capital per capita in equilibrium.